Analysis of legal powers of municipal wardens they possess to ensure safety at the local level - Tičar, Bojan (Varstvoslovje, 2021)
Purpose: This article is primarily intended for students and other professionals at the Faculty of Criminal Justice and Security of the University of Maribor to familiarise themselves with the Slovenian regulation in the field of criminal justice and security. The article presents safety powers of municipal wardens from the perspective of the applicable Slovenian law. Readers may learn how the Slovenian legal system works at the local level, what general legal acts provide a basis for municipal wardens’ actions and what are legal rules for their application. Methods: The article is a scientific review based on grammatical and dogmatic interpretation of applicable legal regulations and selected decisions of the Constitutional Court of the Republic of Slovenia, and on an analytical method (de lege lata) of the review of the Slovenian legislation in the field in question. The legal methods used by the author also include a synthetic method of comparing the legislation from the underlying Municipal Warden Services Act (»Zakon o občinskem redarstvu« ZORed, 2006) and its main amendments set out in the Act Amending the Municipal Warden Services Act (»Zakon o spremembah in dopolnitvah Zakona o občinskem redarstvu« ZORed-A, 2017). Findings: The paper is a comprehensive review of measures that municipal wardens may use to ensure safety at the local level. The author lists the relevant scientific and professional literature and argues about polemic issues with other prominent Slovenian authors dealing with the field in question, i.e., legal powers of municipal wardens. He mainly refers to the works of authors, such as Meško, Žaberl, Dvojmoč, Lavtar, Kečanović, Gostič, Brezovnik, Grafenauer, and Flander. Limitations/Implications: Due to the limited length of the article the overview of the municipal wardens’ powers covers essential legal concepts. The author’s intention is to introduce to the Slovenian or foreign readers the complex notions from the Slovenian legal system, sometimes in a non-technical way since the readers will be both from the field of law and from the field of criminal justice and security. Practical Implications: The article has practical application for domestic and foreign experts wishing to gain knowledge of the Slovenian regulation relating to safety at the local level. Definitions are correct and up-to-date and contribute, therefore, to boosting the knowledge in this field. The article contains a further overview of terms to broaden the understanding of the legal categorical apparatus in local safety and security. Originality/Value: This is a review article and therefore its originality is limited since the author does not provide any new scientific information. Rather, he summarises, through a scientific legal analysis, what is already known. The original value of the article lies in the way the author puts the legal and repressive measures of municipal wardens in a readable and easy-to-understand context so that readers can remember them easily. The definitions of terms used in the article are useful and will be helpful to many readers in their future study or research.
Keywords: local safety and security; lokalna varnost; measures and powers of municipal wardens; municipal and inter-municipal warden services; občinsko in medobčinsko redarstvo; pravica do varnosti; right to security; Slovenian administrative law; slovensko upravno pravo; ukrepi in pooblastila občinskih redarjev